Effect of Fitted Socket Prosthesis on Gait, Performance and Satisfaction Parameters in Below Knee Amputees - M. Naseri; F. Kheyri; H. Nabavi; M.R. Safari (Afarand Scholarly Publishing Institute, 2015)
Aims: Amputation of the lower limbs may lead to physical, psychological and physiological changes in amputated person. This study aimed to investigate the relationship between prosthetic socket status and walking characteristics, the performance and satisfaction of below knee amputates. Materials & Methods: This study was done from the beginning of October to mid-January 2013 at the Red Crescent Society and the University of Social Welfare and Rehabilitation. Samples were selected using convenient sampling. To evaluate the amputee's performance, comfort and satisfaction were measured by Trinity Amputation and Prosthesis Experience Scales and Socket Comfort Score scale. The final analysis of the data was performed using SPSS 19 software and non-parametric Wilcoxon test to compare two related samples in repeated measurements. Findings: Satisfaction with the fitted socket prosthesis was 28.5±1.98 and non-fitted was 22.66±3.55 (p=0.026). Performance restriction using fitted socket prosthesis was 2.50± 2.07, and using non-fitted socket prosthesis was 8.33±1.86 (p=0.024). Psychosocial adaptation using fitted socket prosthesis was 1505±5.16 and using non-fitted socket prosthesis was 14.33±4.08 which was not significantly different (p=0.5). The difference between convenience of amputee using fitted socket prosthesis (8.16±0.75) and non-fitted socket prosthesis (5.23±0.82) was significant (p=0.026). Conclusion: There is a direct relationship between patientchr('39')s feeling comfortable during gaiting and convenience and fitting of prosthetic socket, but there is no relationship between spatial-temporal parameters and speed of walking, except maximum knee folding asymmetry index in the static phase.